Development of a prebiotic blend to influence in vitro fermentation effects, with a focus on propionate, in the gut. Issue 8 (12th July 2021) - Collins, Sineaid M; Gibson, Glenn R; Kennedy, Orla B; Walton, Gemma; Rowland, Ian; Commane, Daniel M
ABSTRACT: Short chain fatty acids (SCFAs) derived from the human gut microbiota, and in particular propionate, may beneficially influence metabolic processes such as appetite regulation. Development of prebiotics that induce high propionate levels during fermentation is desirable. A total of 11 candidate prebiotics were screened to investigate their fermentation characteristics, with a focus on propionate production in mixed anaerobic batch culture of faecal bacteria. Further to this, a continuous 3-stage colonic fermentation model (simulating the human colon) was used to evaluate changes in microbial ecology, lactate and SCFA production of three 50:50 blends, comprising both slow and rapidly fermented prebiotics. In mixed batch culture: xylo-oligosaccharide, polydextrose and α-gluco-oligosaccharide were associated with the greatest increase in propionate. Polydextrose, α-gluco-oligosaccharide, β-1, 4 glucan and oat fibre induced the greatest reductions in the acetate to propionate ratio. The most bifidogenic prebiotics were the oligosaccharides. Fermentation of a 50:50 blend of inulin and arabinoxylan, through the continuous 3-stage colonic fermentation model, induced a substantial and sustained release of propionate. The sustained release of propionate through the colon, if replicable in vivo, could potentially influence blood glucose, blood lipids and appetite regulation, however, dietary intervention studies are needed. Bifidogenic effects were also observed for the inulin and arabinoxylan blend and an increase synthesis of butyrate and lactate, thus indicating wider prebiotic potential. Abstract : Screening candidate prebiotics to identify high propionate producers and go on to develop prebiotic blends that induce sustained propionate production in the gut to improve the metabolic health of the host.